2019
DOI: 10.1038/s41598-019-51782-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of suitable controls for miRNA quantification in T-cells and whole blood cells in sepsis

Abstract: Complex immune dysregulation is a hallmark of sepsis. The occurring phases of immunosuppression and hyperinflammation require rapid detection and close monitoring. Reliable tools to monitor patient’s immune status are yet missing. Currently, microRNAs are being discussed as promising new biomarkers in sepsis. However, no suitable internal control for normalization of miRNA expression by qPCR has been validated so far, thus hampering their potential benefit. We here present the first evaluation of endogenous co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Although miR-150 has been previously revealed to serve key roles in diabetes and other autoimmune diseases ( 45 ), the role of this miRNA in sepsis remains unclear. In the present study, it was confirmed that miR-150 expression was downregulated in LPS-stimulated THP-1 cells, consistent with the reduced miR-150 expression observed in patients with sepsis ( 46 ). Results from the present study also demonstrated that miR-150 functioned as a negative regulator of the macrophage inflammatory response by suppressing the production of pro-inflammatory cytokines IL-1β, IL-6 and TNF-α.…”
Section: Discussionsupporting
confidence: 91%
“…Although miR-150 has been previously revealed to serve key roles in diabetes and other autoimmune diseases ( 45 ), the role of this miRNA in sepsis remains unclear. In the present study, it was confirmed that miR-150 expression was downregulated in LPS-stimulated THP-1 cells, consistent with the reduced miR-150 expression observed in patients with sepsis ( 46 ). Results from the present study also demonstrated that miR-150 functioned as a negative regulator of the macrophage inflammatory response by suppressing the production of pro-inflammatory cytokines IL-1β, IL-6 and TNF-α.…”
Section: Discussionsupporting
confidence: 91%
“…Expression of mRNA was determined using a LightCycler 480 instrument (Roche Diagnostics, Mannheim, Germany) as previously described (Möhnle et al , 2018 ; Hirschberger et al , 2019 ). All analyses were calculated using duplicate values.…”
Section: Methodsmentioning
confidence: 99%
“…U6 is one of the most commonly employed, although its use is a matter of debate; it is not properly a miRNA [ 28 , 30 ]. Some studies have indicated its unsuitability for miRNA normalization due to expression instability in various experimental conditions [ 31 , 32 , 33 ]. Conversely, in other models, U6 expression levels are very stable among the sample groups, making it a valid endogenous control [ 30 , 34 ].…”
Section: Discussionmentioning
confidence: 99%